Pemberdayaan Kelompok Tani Dalam Pemanfaatan Teknologi Tepat Guna Untuk Meningkatkan Produktivitas Pertanian Di Desa Sukajadi Kecamatan Sadananya - Fitri Adila Novianti; Irfan Nursetiawan; Muhammad Sobari; Riris Risnawati; Ujang Irman Saputra (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
This study aims to empower farmer groups in applying appropriate technology to rice farming productivity in Sukajadi Village, Sadananya District, Ciamis Regency. The research methods used include field surveys and analysis of productivity data from farmers who apply this technology compared to those who do not. Primary data was collected through structured interviews with farmers and direct observation in the field during the research period. Data analysis was carried out by comparing rice production results, efficiency of using agricultural inputs, and farmer income before and after adopting appropriate technology. The research results show that the adoption of appropriate technology significantly increases rice productivity in terms of the number of harvests per hectare and reduces the costs of certain inputs such as fertilizers and pesticides. In addition, farmers who apply this technology also report better income increases compared to conventional methods. These findings support the importance of implementing appropriate technology in improving food security and the economy of farmers in rural areas such as Sukajadi Village. This research contributes to expanding understanding of the practical benefits of appropriate technology in the context of rice farming in Indonesia.